CHARACTERISTICS OF ACTIVE AERIALS OF ONBOARD AVIATION NAVIGATION-LANDING EQUIPMENT - Кондрашов, Я.В.; Осіпчук, А.О. (Science-based technologies, 2013)
Active aerials (AA) or aerials-strengtheners are devices, that unite aerial and active elements of strengthening, transformation or generation of signals. Integration of aerials and active elements allows to decrease the sizes of aerials, to extend the band pass of aerials, to improve the sensitiveness of receiving aerials, carry out the electronic tuning of aerials, to increase effective antenna balance with transmission line, to improve electromagnetic compatibility of the radiosystems. Electromagnetic compatibility (ЕМС) of АА is determined by next characteristics: a dynamic range, blocking, intermodulation, cross modulation. Quantitative characteristics of EMC AA onboard aviation navigation-landing equipment of IV generation determined as to field strengths of noises and signals that is set by the requirements of ARINC and NLGS 3. Are represented the researches technique of characteristics of active aerials navigation landing apparatus in ground or in laboratory terms by means of standard measuring apparatus. The results of measuring showed that technical requirements to characteristic of ЕМС active aerial AP-001M of course receiving apparatus were executed in part: of dynamic range, blocking, mutual and cross modulation, and also intermodulation.